Soldier from subterranean termites Coptotermes curvignathus eject a poison secretions as a defensive secretions to overcome their enemy. This research aimed to evaluation the toxicity of soldier defensive secretions extract in aquabidestilata, ethanol, ethyl acetate and n-hexane solutions against Odontoponera denticulata ants. Filter paper with 200 µl extract were exposure to ants for 14 day. The first time ants mortality and time for all ants mort - Farah DIBA; Dodi NANDIKA (Jurnal Ilmu dan Teknologi Hasil Hutan, 2009)
Soldier from subterranean termites Coptotermes curvignathus eject a poison secretions as a defensive secretions to overcome their enemy. This research aimed to evaluation the toxicity of soldier defensive secretions extract in aquabidestilata, ethanol, ethyl acetate and n-hexane             solutions against Odontoponera denticulata ants. Filter paper with 200 µl extract were exposure to ants for 14 day.                    The first time ants mortality and time for all ants                  mortality were recorded. Result of the research showed that the first time ants mortality was on ethanol extract (15 minutes                after exposure), then followed on ethyl acetate extract,                  n-hexane extract and aquabidestilata extract for 30, 35 and 40 minutes respectively.The faster time for all ants mortality            was on ethanol extract (54 hour), then followed by ethyl acetate  extract, n-hexane extract and aquabidestilata extract for 74, 79 and 82 hour respectively. GCMS analysis showed that the bioactive compound on ethanol extract were pentadecanal and tetradecanal.   Keywords : Soldier defensive secretions, toxicity, Coptotermes curvignathus, Odontoponera denticulata